Konstribusi Makanan Terhadap Prilaku Manusia - Suaidi Suaidi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The development of the times not only shifts morality, but also makes behavior drift and tends to shift cultural values, where human life is now almost separated from the cultural heritage of ancestors. The culture of mutual cooperation has changed into an individualistic culture of life so that social concern and sensitivity are no longer part of life's needs. Shifts in cultural values and lifestyle also influence food consumption behavior. Where humans in this modern era are more inclined to consume food that is in accordance with the times. The choice is that for the sake of prestige, the legal status of food is no longer a consideration. Halal and haram are not a criterion. Islam as a religion pays attention to food consumption. In principle, food must be useful for human survival, as an ingredient to improve the quality of worship as an obligation for His servants to Allah, SWT. Therefore, consuming food must be sterile from uncleanliness because the substance, method of obtaining and processing the food before consumption must ensure that it is halal. Because, Islam views that food is closely related to human behavior, haram food contributes to human behavior to bring harm to other humans.